Management of severe fetal anemia by Doppler measurement of middle cerebral artery: are there other benefits than reducing invasive procedures?. (September 2015) - Garabedian, C.; Vaast, P.; Behal, H.; Coulon, C.; Duahamel, A.; Thomas, D.; Rakza, T.; Subtil, D.; Houfflin-Debarge, V.
Abstract: Objective: Doppler measurement of peak velocity of systolic blood flow in the middle cerebral artery (PVS-MCA) can safely replace invasive testing in the diagnosis of fetal anemia in Rh-alloimmunized pregnancies and PSV-MCA is now the reference technique. However, no study has evaluated its impact in antenatal care and in survival rate. Our objective was to evaluate the impact of the measurement of PVS-MCA in antenatal management and neonatal outcome in maternal red cell alloimmunization requiring in utero transfusion (IUT). Study design: Retrospective study between January 1999 and January 2013. We excluded all cases of hydrops without follow-up before first IUT. From 1999 to 2006, an IUT was indicated on the optical index at 450 nm (Period 1) and was then replaced by the use of PVS-MCA (Period 2). Results: 77 patients were included, 39 in Period 1 (104 IUT) and 38 in Period 2 (89 IUT). 5 cases of hydrops fetalis (12.8%) were diagnosed during the follow up in Period 1 and none during Period 2. The average number of IUT, the delays between 2 IUT and between last IUET and birth were comparable. The total rate of complication per IUT during the first period was 9.6% vs 1.1% during the second one ( p = 0.01). The overall survival rate in our population was 34/39 (86.8%) during Period 1 vs 38/38 (100%) during Period 2. Conclusion: PSV-ACM allowed an improved monitoring with fewer occurrences of hydrops. Conversely, it did not modify antenatal management and timing of delivery.